Exiting the Anthropocene: Achieving personal and planetary health in the 21st century. Issue 12 (6th July 2022) - Prescott, Susan L.; Logan, Alan C.; Bristow, Jamie; Rozzi, Ricardo; Moodie, Rob; Redvers, Nicole; Haahtela, Tari; Warber, Sara; Poland, Blake; Hancock, Trevor; Berman, Brian
Abstract: Planetary health provides a perspective of ecological interdependence that connects the health and vitality of individuals, communities, and Earth's natural systems. It includes the social, political, and economic ecosystems that influence both individuals and whole societies. In an era of interconnected grand challenges threatening health of all systems at all scales, planetary health provides a framework for cross‐sectoral collaboration and unified systems approaches to solutions. The field of allergy is at the forefront of these efforts. Allergic conditions are a sentinel measure of environmental impact on human health in early life—illuminating how ecological changes affect immune development and predispose to a wider range of inflammatory noncommunicable diseases (NCDs). This shows how adverse macroscale ecology in the Anthropocene penetrates to the molecular level of personal and microscale ecology, including the microbial systems at the foundations of all ecosystems. It provides the basis for more integrated efforts to address widespread environmental degradation and adverse effects of maladaptive urbanization, food systems, lifestyle behaviors, and socioeconomic disadvantage. Nature‐based solutions and efforts to improve nature‐relatedness are crucial for restoring symbiosis, balance, and mutualism in every sense, recognizing that both personal lifestyle choices and collective structural actions are needed in tandem. Ultimately, meaningful ecological approaches will depend on placing greater emphasis on psychological and cultural dimensions such as mindfulness, values, and moral wisdom to ensure a sustainable and resilient future.